Characterization of biodiesel production from moringa oleifera - Iqmal Hakim, Mohd Kordi (2014)
The combustion of fossil fuel lead to releases various type of gases like carbon dioxide, carbon monoxide and other toxic gases that can cause air pollution. When there is a significant rise in the percentage of carbon dioxide in the air, the amount of heat captured by the carbon dioxide gas also increases. This is turn leads to overall rise in the surface temperature of the earth which known as global warming. Biodiesel is now being recognised as one alternative to replace fossil fuel. Biodiesel is a renewable, degradability and environmentally friendly resources. It is produced from vegetable oils, animal fats or waste cooking oils and can be used in existing diesel engine without any expensive modification. Although biodiesel produces less emission than fossil fuel diesel, it requires investigation and evaluate some properties and chemical composition of the oil, as well any potential application in biodiesel production. This paper present the properties of biodiesel production from Moringa oleifera seeds as a candidate for biodiesel production. Moringa oleifera is considered as a versatile plant due to its multiple uses. Moringa oleifera also has been found to be potential new sources of oil and this plant sill one of the under explored plants and there is lack of information about physic-chemical properties of the seed oil which has limited their applications. Extraction method is used to extract the Moringa oil by using Soxhlet and n-hexane as a solvent. Moringa oleifera biodiesel is obtained by a transesterification process with methanol and potassium hydroxide as catalyst. The biodiesel properties are measured using ASTM methods. The results showed that Moringa oleifera biodiesel have cetane number of 67, kinematic viscosity value is 4.8 mm2/s, 165 °C for the flash point and density is 875 kgm-3. The cloud point and pour point for Moringa oleifera methyl ester are 18 °C and 17 °C respectively and the acid value is 0.41 mg KOH/g.